2024
DOI: 10.1016/j.jvoice.2021.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Masking Habits on Voice in a Sub-population of Healthcare Workers

Abstract: Objective To evaluate the impact of face masks on voice in a sub-population of healthcare workers, namely residents, medical students, and nurses, during the COVID-19 era. Materials and Methods A cross-sectional study was conducted in a large tertiary care center where a 23-items web-based questionnaire was conveyed to sub-population of healthcare professionals, namely residents, medical students, and nurses. The questionnaire included demographic data, type, and durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Due to minimal changes in the outcomes of the acoustic parameters between the recordings, a clinical significance could not be clearly observed. Although wearing masks for a prolonged period of time may cause observable self-perceived changes (e.g., breathing difficulties, increased effort of speaking, greater perception of symptoms of vocal fatigue and discomfort and changes in speaking behavior) in wearers [ 32 , 33 , 34 , 35 ], this influence remains unexplained in the present study, notwithstanding the fluctuations in multiple recordings of the voice analyses. To verify mask effects after prolonged wearing, it should be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 79%
“…Due to minimal changes in the outcomes of the acoustic parameters between the recordings, a clinical significance could not be clearly observed. Although wearing masks for a prolonged period of time may cause observable self-perceived changes (e.g., breathing difficulties, increased effort of speaking, greater perception of symptoms of vocal fatigue and discomfort and changes in speaking behavior) in wearers [ 32 , 33 , 34 , 35 ], this influence remains unexplained in the present study, notwithstanding the fluctuations in multiple recordings of the voice analyses. To verify mask effects after prolonged wearing, it should be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 79%
“…In an analysis to compare differences between sex and six different mask conditions (no mask, cloth mask, surgical mask, N95 mask, and surgical mask over an N95 mask with and without face shield) for measures of voice intensity and acoustic variables, it was found that tested masks did not have a significant impact on loudness, fundamental frequency, PPC-s compared to the unmasked voice output; however, using a face shield affected vocal intensity and PPC-s ( 46 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The Impact of Masking Habits on Voice in a Subpopulation of Healthcare Workers (46) Lebanon and USA, 2022…”
Section: IVmentioning
confidence: 99%
“…The Impact of Masking Habits on Voice in a Subpopulation of Healthcare Workers (46) Líbano e EUA, 2022…”
Section: IVmentioning
confidence: 99%
“…Em uma análise para comparar diferenças entre sexo e seis diferentes condições de máscaras (sem máscara, máscara de pano, máscara cirúrgica, máscara N95 e, máscara cirúrgica sobre uma máscara N95 com e sem protetor do tipo face shield) quanto às medidas de intensidade e variáveis acústicas da voz, verificou-se que as máscaras testadas não tiveram um impacto significativo na intensidade, frequência fundamental, PPC-s em comparação com a saída de voz sem máscara, mas o uso do protetor facial (face shield) afetou a intensidade vocal e os PPC-s (46) . Profissionais de saúde relataram um aumento significativo do esforço vocal a jornada de trabalho (21) .…”
Section: Dados De Características Dos Equipamentos De Proteção Indivi...unclassified